Traditional sectors based on natural resources – a blessing or a curse for less developed regions? A case study of Podlaskie Voivodeship - Dąbrowska Anna (Miscellanea Geographica: Regional Studies on Development, 2017)
The natural environment, as a source of natural resources, has long been perceived as being a factor in determining the development of many states and regions, especially less developed areas. The main research question in this article is what role is played by natural resources and traditional industry sectors based on natural resources (milk production and tourism), in the process of establishing a competitive advantage for Podlaskie Voivodeship, which is one of the less developed regions in Poland. The results of the research reveal weaknesses that are inherent in earlier ways of thinking about these industries and, at the same time, emphasise the importance of making use of natural resources in an integrated way and combining them with new technologies.